Improvement Of Free Convection From Three horizontal Finned Cylinders Fixed Between Two Walls - Hassan K. Abdullah; Haneen H. Rahman (Wasit Journal of Engineering Sciences)
Improvement of  free convection heat transfer from three finned cylinders arranged at a triangle shape fixed between two walls has been investigated in this study. Three mild steel finned cylinders fixed between two walls from Pyrex glass have been used as a test rig. It has been changed the spacing between the cylinders (X/D=1,2,3 & S/D=2,4,6) and the head orientation of a triangle to the top under constant heat flux values (38, 254, 660, 1268) W/m2 and compare with case of three finned cylinders arranged in vertical array in line fixed between two wall. The experiments are carried for Rayleigh number (Ra) from (15x103 to 14 x104 ) and Prandtl  number from (0.706-0.714 ). The results indicated an increase in Nu with increasing Ra for all cylinders. Furthermore,hx and Nu increased proportionally with the increasing of cylinder spacings for all heat fluxes. Also the experimental results show the case of triangle arrangement is improvement the heat transfer more than case of vertical arrangement. Heat transfer dimensionless correlating equation is also proposed.